MINAT WISATAWAN NUSANTARA DAN PENGARUNYA TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI JAWA BARAT - Devira Maharani Wiharja (2022)
Regional Original Revenue aims to provide and allocate the necessary funds for both the central and local governments, these funds come from several sources, one of which is local taxes and regional levies which are included in the contribution of the tourism sector. In the tourism sector, it is usually supported by the factors of tourists who come to visit and the attractions provided. Tourists who come to visit usually come to fulfill their tertiary needs and look for free time when they are free from daily work to get entertainment, that is why tourists are looking for a suitable tourist attraction for them to visit so that their desire to have vacation time is fulfilled. With the arrival of certain tourists at some of these attractions, indirectly the local revenue is fulfilled when the money that tourists use in these attractions is included in the regional taxes and levies and becomes local revenue. This study is a quantitative study that aims to determine the effect of Population, Tourists, and Tourist Attractions on Regional Original Income in West Java for the period 2017 to 2019. The method chosen is the Fixed Effect Model (FEM). The results of this study indicate that (1) Population has an effect on Regional Original Income in West Java (2) Tourists have an effect on Regional Original Income in West Java (3) Tourism objects have no effect on Regional Original Income in West Java.